New lectotypifications and new synonyms in Festuca (Poaceae, Pooideae, Loliinae) from the Central Andes - Ospina, Juan C. (Phytotaxa, 2016)
New lectotypifications and new synonyms are provided as a result of a systematic study of the genus Festuca from the Central Andes. In the Andes mountains of Argentina, Bolivia, and Chile, several species of Festuca are dominant components of the grasslands and high Andean steppes. Festuca circinata and F. dissitiflora occur in this area and were described based on morphological characters. Some authors have considered F. circinata as a valid species while others have treated it as a synonym of F. dissitiflora, together with F. dissitiflora var. loricata , F. dissitiflora var. villipalea, and F. erecta var. aristulata. In this study, a review of the taxonomy and nomenclature of F. castilloniana, F. circinata, and F. potosiana was performed, and their morphological and anatomical characters were compared with F. dissitiflora. Based on morphoanatomical and epidermal characters, this study contributes to the delimitation of F. circinata and F. dissitiflora. Nomenclatural notes and new anatomical and epidermal descriptions are included for these species. Differential characters between F. circinata and F. dissitiflora are discussed and F. circinata is restored as a valid species for Argentina. Festuca castilloniana and F. potosiana are synonymised under F. dissitiflora. Festuca dissitiflora var. loricata, F. dissitiflora var. villipalea, and F. erecta var. aristulata are excluded from the synonymy of F. dissitiflora and it is suggested that these names should be subordinate under F. fiebrigii. Festuca stuckertii is proposed as a new synonym of F. uninodis. Lectotypes are designated for the names F. argentinensis, F. dissitiflora, F. nemoralis and F. parodii, and second-step lectotypes are designated for the names F. circinata and F. ampliflora.